Peran Struktur Modal dalam Memediasi Pengaruh Firm Size dan Profitabilitas terhadap Nilai Perusahaan Sub Sektor Makanan dan Minuman - Priyanto, Sugeng; Riyadi, Selamet (Jurnal Ilmu Manajemen, 2023)
This research aims to determine the role of capital structure in mediating the influence of firm size and profitability on company value. This research uses secondary data with a population of 43 food and beverage companies listed on the Indonesia Stock Exchange with the observation year 2018-2022.The sampling technique used in this research is purposive sampling with multiple linear regression analysis and path analysis methods.The results of this research show that firm size, profitability as proxied by return on equity have a positive and significant influence on capital structure, firm size has a negative and significant influence on firm value, profitability as proxied by return on equity and capital structure have a positive and significant influence on value. company, capital structure is able to mediate the influence of firm size on company value and capital structure is not able to mediate the influence of profitability on company value.